Transport and Logistics : Myanmar Infrastructure Monitoring - World Bank (Washington, DC: World Bank, 2022)
Transport and logistics services in Myanmar have been substantially hit by the impacts of the February 2021 coup and the surge in Coronavirus disease 2019 (COVID-19) cases. Logistics companies have been affected by rising fuel prices, border closures, and a shortage of shipping containers. While the initial effects after the military coup on the transport sector were extremely severe, there have been signs of some recovery of transport services since May 2021. Public transport in Yangon experienced a significant reduction in passenger demand in early months after the coup, subsequently recovering some ground by December 2021. Higher fuel prices and currency liquidity shortages significantly increased the cost of inland transport services. Transportation and logistics services are expected to be severely impacted by continuing high fuel prices, mobility constrains, political instability, and evolution of the pandemic. The export and import via container are expected to recover gradually due to agricultural and garment industry-led demand. However, improvement of exports and imports in the medium term is uncertain given the complexity of trade relations with international trade partners. In addition to effects of the coup and political conflicts, risks related to the pandemic will also significantly impact logistics supply chains and mobility in the near to mid-term.